THE USE OF MORPHOLOGICAL AWARENESS TO IMPROVE STUDENTS’ VOCABULARY KNOWLEDGE - Ulma Nadilah; Ana Kuliahana; Andi Muhammad Dakhalan (Datokarama English Education Journal, 2023)
Vocabulary plays an important role in language acquisition. By mastering vocabulary, the students can express their idea easily. The reality, many students have a limited vocabulary. This paper focuses on the use of morphological awareness to increase students' vocabulary knowledge. The researcher applied Quantitative Research. The instrument used to collect the data was tests. The pre-test is to determine the level of students' vocabulary mastery before being given the treatment, while the post-test test is used to find out the results after being given the treatment. There is a significant difference between pre-test and post-test scores, there is a morphological effect on vocabulary knowledge at Ma'had Al-Jamiah IAIN Palu with foreign languages. This is evidenced by the results obtained where the final result of the average value of students is 67.2 while the previous grade was 34 and has increased by about 97%. This research is in accordance with the target. Thus, there is a significant increase after being given the treatment of Using Morphological Awareness to Increase Students' Vocabulary Knowledge.